Knowledge mapping and visualization analysis of pelvic organ prolapse repair with mesh from 2001 to 2021 - Zhou, Quan; Lu, Man; Li, Guo-Sheng; Peng, Gan-Lu; Song, Yan-Feng (Frontiers in Bioengineering and Biotechnology, 2023)
Aims: In recent decades, extensive attention has been paid to the application of mesh to repair pelvic floor defects. However, a large body of related literature has not been system summarized. The purpose of this study is to summarize and visualize the literature on pelvic organ prolapse (POP) repair with mesh using bibliometrics. Methods: Medical literature regarding POP repair with mesh were searched and obtained in the Web of ScienceTM Core (WoSCC) database from 2001 to 2021. Microsoft Excel 2020, CiteSpace and VOSviewer were used to conduct the bibliometric and knowledge-map analysis. Results: In the past 20 years, a total of 2550 articles and reviews have been published in 35 journals, and the published and cited results show a growing trend. Cosson M and International Urogynecology Journal were the authors and journals with the highest output, respectively. The United States, France and the United Kingdom are among the top three countries/organizations in relevant publications in worldwide. 584 key words in the literature are divided into 8 clusters, which are mainly related to prolapse type, risk factors, surgical methods, imaging, quality of life and bioengineering. Using clinical research and tissue engineering technology to reduce mesh complications is the current hot spot in this field. Conclusions: Reasonable application of mesh and avoiding mesh complications are still the most concerned topics in POP research. Although clinical research, surgical improvement, biological mesh and bioengineering technology have shown promising results, it is still urgent to carry out clinical transformation application research.